Recent Advances in Our Understanding of the Biosynthesis of Sulfur Modifications in tRNAs - Shigi, Naoki (Frontiers in Microbiology, 2018)
Sulfur is an essential element in all living organisms. In tRNA molecules, there are many sulfur-containing nucleosides, introduced post-transcriptionally, that function to ensure proper codon recognition or stabilization of tRNA structure, thereby enabling accurate and efficient translation. The biosynthesis of tRNA sulfur modifications involves unique sulfur trafficking systems that are closely related to cellular sulfur metabolism, and ‘modification enzymes’ that incorporate sulfur atoms into tRNA. Herein, recent biochemical and structural characterization of the biosynthesis of sulfur modifications in tRNA is reviewed, with special emphasis on the reaction mechanisms of modification enzymes. It was recently revealed that TtuA/Ncs6-type 2-thiouridylases from thermophilic bacteria/archaea/eukaryotes are oxygen-sensitive iron-sulfur proteins that utilize a quite different mechanism from other 2-thiouridylase subtypes lacking iron-sulfur clusters such as bacterial MnmA. The various reaction mechanisms of RNA sulfurtransferases are also discussed, including tRNA methylthiotransferase MiaB (a radical S-adenosylmethionine-type iron-sulfur enzyme) and other sulfurtransferases involved in both primary and secondary sulfur-containing metabolites.